2023
DOI: 10.3390/horticulturae9040466
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Glucosinolate and Phenolic Compounds in Green and Red Kimchi Cabbage (Brassica rapa L. ssp. pekinensis) Hairy Roots after Exposure to Light and Dark Conditions

Abstract: Brassica rapa L. ssp. pekinensis (Lour.) Hanelt (kimchi cabbage) is a major vegetable cultivated in Korea, and its hairy roots (HRs) are rich in glucosinolates and phenolic compounds. This study aimed to induce HRs from cotyledon explants via the transformation of the Agroacterium rhizogenes strain R1000 and examine the glucosinolate and phenolic compounds present in the HRs of two kimchi cabbage (green and red) cultivars after exposure to 16 h light/8 h dark conditions (photosynthetic photon flux density of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…42 filter paper, the supernatant samples were transferred to new tubes and stored in vials for HPLC analysis. HPLC analysis and conditions were like those in a previous study . The retention times of the standard and spike tests were used to specify the peaks in the extract.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 filter paper, the supernatant samples were transferred to new tubes and stored in vials for HPLC analysis. HPLC analysis and conditions were like those in a previous study . The retention times of the standard and spike tests were used to specify the peaks in the extract.…”
Section: Methodsmentioning
confidence: 99%
“…HPLC analysis and conditions were like those in a previous study. 20 The retention times of the standard and spike tests were used to specify the peaks in the extract. Also, quantification was performed through each calibration curve of 12 compounds ( Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With some modifications, GSLs were extracted using previously reported procedures. 52 Briefly, 100 mg of a freeze-dried powdered sample was collected in a 2 mL Eppendorf tube, and 1.5 mL of methanol was added. For 5 min, the tubes were placed in a water bath at 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Galantamine is an alkaloid from the Amaryllidaceae family. It is a dibenzofuran-type base that has been found in several species of this family. , Acetylcholinesterase inhibitor galantamine is a powerful drug used worldwide to treat the symptoms of Alzheimer-type senile dementia. , The galantamine used in the medical field can be produced in two ways, total synthesis and extraction, using Amaryllidaceae plants. , Phenylpropanoids comprise a broad group of organic compounds that are synthesized by a combination of the amino acids tyrosine and phenylalanine in plants. , Previous studies have reported that phenylpropanoids have various positive benefits for human health (helps to prevent diabetes, cancer, and heart disease) and pharmaceutical sectors. …”
Section: Introductionmentioning
confidence: 99%